TECHNOLOGICAL INNOVATIONS IN MEDICAL TECHNICAL EDUCATION - Muxiddinova, Marg‘uba Xodjiakbarovna; Urakova, Nargiza Nurillayevna (Educational Research in Universal Sciences, 2024)
This article highlights the need for medical educators to incorporate new technologies into their curricula to keep pace with the evolving healthcare industry. Additionally, by integrating technologies such as virtual reality, simulation tools, and advanced medical equipment into medical technician education, students need to be better equipped to gain hands-on experience and develop the skills necessary to excel in their future careers.